Perkembangan Manado Masa Kolonial (1789-1945) - Irfanuddin Wahid Marzuki (Tumotowa, 2020)
Manado has been the capital of the region since the colonial period, starting from the VOC, the Dutch East Indies, until now. Nowadays, the development made the old city area of Manado have no longer trace. Few people know this area because there are no archeological remains in the old city of Manado. The purpose of writing to find out the background of the selection of the location of the city of Manado and the development of the colonial city. The method used in this study is urban archeology. The results showed the geographical condition of the Manado coast which was flat, near the river mouth and there were no settlements before it became a consideration for Europeans making settlements. The forerunner of the city of Manado began with Loji, fortresses, ports, and developed into an administrative city. The development of administrative status improves the facilities and spatial management of the city of Manado.